Identification of Mycobacterium genavense natural infection in a domestic ferret. (January 2019) - Dequéant, Bérengère; Pascal, Quentin; Bilbault, Héloïse; Dagher, Elie; Boschiroli, Maria-Laura; Cordonnier, Nathalie; Reyes-Gomez, Edouard
A 6-y-old neutered male ferret ( Mustela putorius furo ) was presented because of a 1-mo history of progressive weight loss, chronic cough, and hair loss. On clinical examination, the animal was coughing, slightly depressed, moderately hypothermic, and had bilateral epiphora. Thoracic radiography was suggestive of severe multinodular interstitial pneumonia. Abdominal ultrasound examination revealed hepatosplenomegaly and mesenteric and pancreaticoduodenal lymphadenopathy. Fine-needle aspiration of the pancreaticoduodenal lymph node, followed by routine Romanowsky and Ziehl–Neelsen stains, revealed numerous macrophages containing myriad acid-fast bacilli, leading to identification of mycobacteriosis. Autopsy and histologic examination confirmed the presence of disseminated, poorly defined, acid-fast, bacilli-rich granulomas in the pancreaticoduodenal and mesenteric lymph nodes, intestines, and lungs. Destaining of May-Grünwald/Giemsa–stained slides with alcohol, and then restaining with Ziehl–Neelsen, revealed acid-fast rods and avoided repeat tissue sampling without affecting the Ziehl–Neelsen stain quality and cytologic features. Tissue samples were submitted for a PCR assay targeting the heat shock protein gene ( hsp65 ) and revealed 100% homology with Mycobacterium genavense. We emphasize the use of special stains and PCR for identification of this potential zoonotic agent.